1997
DOI: 10.1080/00480169.1997.36018
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the eruption of the permanent incisor teeth of farmed Javan rusa deer (Cervus timorensis russa) in New Caledonia

Abstract: The eruption of the permanent incisor teeth of 14 farmed Javan rusa deer (Cervus timorensis russa) of known birth date and their live weights were observed about every 2 weeks from 12 to 30 months of age. The permanent incisor pattern was 11, 14-17 months; 12, 18-23 months; 13, 20-26 months; and 14, 22-27 months. There was no significant relationship between body weight and timing of permanent incisor eruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Consistency between the two iterations was high for both methods, but in both cases discrepancies were more likely to occur in older animals (Table 1). Previous studies have found that accurate age estimation by TEW is more difficult in older than in younger animals (Jacobson & Reiner 1989, Ratcliffe & Mayle 1992, Bianchi et al 1997). In our study the animals with assigned ages that varied by two years using TEW were estimated to be 3‐5 years old or older.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistency between the two iterations was high for both methods, but in both cases discrepancies were more likely to occur in older animals (Table 1). Previous studies have found that accurate age estimation by TEW is more difficult in older than in younger animals (Jacobson & Reiner 1989, Ratcliffe & Mayle 1992, Bianchi et al 1997). In our study the animals with assigned ages that varied by two years using TEW were estimated to be 3‐5 years old or older.…”
Section: Resultsmentioning
confidence: 98%
“…In many wild ungulate species (e.g. Javan rusa deer Cervus timorensis russa, red deer Cervus elaphus, fallow deer Dama dama and roe deer Capreolus capreolus ), eruption of permanent teeth is complete by 18‐36 months, so aging beyond this limit is more difficult (Brown & Chapman 1991b, Brown & Chapman 1991a, Ratcliffe & Mayle 1992, Moore, Cahill, Kelly & Hayden 1995, Bianchi, Hurlin, Lebel & Chardonnet 1997, Langvatn & Meisingset 2001).…”
Section: Methods For Age Estimation In Ungulatesmentioning
confidence: 99%